Implementation of DHCP Snooping Method to Improve Security on Computer Networks - Andi Purnomo (Komunitas Dosen Indonesia, 2024)
This research proposes the DHCP Snooping method which is used to increase security on computer networks because Dynamic Host Configuration Protocol (DHCP) is a potential target for computer network attacks, one of the attack gaps that can occur in DHCP is the DHCP Rogue attack which is the simplest hacking method in which the attacker creates a fake DHCP connected to the core network allowing the hacker to set up a fake DHCP Server with full access to distribute IP addresses to clients. To address security gaps in computer networks in this research, researchers applied the DHCP Snooping method, which is a series of techniques to improve DHCP network security. When the DHCP server allocates IP addresses to clients on the LAN, DHCP Snooping can be configured on the LAN switch to allow only clients with certain IP and MAC addresses to have access to the network. By implementing the DHCP Snooping method you can increase security on computer networks where DHCP Snooping can distinguish which ports can be trusted (Trusted Port) and which ports cannot be trusted (Untrusted Port) so that the security of data and information in the computer network is maintained properly. Based on the results of this research, DHCP Snooping can prevent clients from getting DHCP IPs from DHCP Rouge because it has determined Trusted Port and Untrusted Port.